Vision: Leveraging Low Earth Orbit Satellites for Future Ubiquitous Positioning - Sherif Mostafa (13548916) (2024)
Designing a globally ubiquitous positioning system that works seamlessly in all environments remains a critical area of ongoing research. While Global Navigation Satellite Systems (GNSS), such as GPS, are the predominant technology for global outdoor positioning, they fail in areas with physical obstructions (e.g., dense urban regions and indoors) and are prone to jamming. These limitations significantly restrict their global accessibility and dependability, highlighting the need for supplementary positioning technologies. Recently, private companies like SpaceX have started deploying Low Earth Orbit (LEO) satellites for various applications, primarily communication. LEO satellites operate at much lower altitudes than GNSS satellites, offering higher signal penetration capabilities and reduced susceptibility to jamming, making them a promising complementary positioning technology. In this paper, we present our vision for opportunistically leveraging LEO satellite signals to achieve ubiquitous and reliable global positioning. We explore diverse opportunities enabled by our vision and discuss the multi-disciplinary challenges that must be addressed for its realization. Other Information Published in: Proceedings of the 32nd ACM International Conference on Advances in Geographic Information Systems License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1145/3678717.3691251